Factors Causing Lack of Interest in Clinical Research Among Postgraduate Trainees at Peoples University of Medical & Health Sciences for Women, Shaheed Benazir Abad. A Mixed Method Study - Rafia Tabassum, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Conduct of clinical research requires time, resources, dedication, enthusiasm, willingness, knowledge, training of research methodology, and practical skills. Postgraduate medical students show lack of interest towards clinical research attributed to a diverse group of causes. Objectives: The objective of current mixed method study was to evaluate factors contributing to lack of interest in clinical research among PG trainees at PUMHSW SBA. Methodology: After taking approval from the Institutional Ethical review committee and obtaining written informed consent from the 50 participants selected by purposeful sampling. Two focus group discussions (FGD) were arranged, which were recorded and transcribed. Thematic content analysis of these transcripts was carried out. In the subsequent phase the predesigned validated questionnaire was used and analyzed using descriptive statistics. Results: A total of 92% (46/50) responded, of those 21 were females. The knowledge regarding research and its methodology was 89-93%. Eighty-nine percent strongly agreed to include research in the curriculum and believed that it would facilitate better patient outcome and clinical practice (89.1%). All respondents opined that faculty and mentors play a crucial role in the conduct of research. Factor hindering interest in research were lack of previous exposure to research (54.3%), lack of research curriculum (45.7%), deficient statistical support (43.5%), disinterested faculty (30.4%), lack of time due to heavy ward duties (39.1%), and family commitments (37%). Practical Implication: Conduct of clinical research requires time, resources, dedication, enthusiasm, willingness, knowledge, training of research methodology, and practical skills. Current study will provide help to the new researchers to solve their research hazards for new and innovative developments. Conclusion: Majority of the participants had some knowledge about research and its positive impacts on clinical practice. Factors identified to cause lack of interest included lack of research curriculum, statistical support, time, previous knowledge, financial and family issues. Keywords: Clinical research, factors, lack of interest, attitude, post graduate trainees.